Islam, Indian religions, and Tamil culture - Sulaiman, S. M., 1919-; Ismāyil, Mu. Mu., 1921- (Dr. S. Radhakrishnan Institute for Advanced Study in Philosophy, University of Madras, 1977)
Lectures delivered at Dr. S. Radhakrishnan Institute for Advanced Study on Islam and Tamil culture during 1977; a golden jubilee publication.